2015
DOI: 10.1007/s00394-015-1041-8
|View full text |Cite
|
Sign up to set email alerts
|

Intake and sources of added sugars among Australian children and adolescents

Abstract: A large proportion of Australian youths are consuming excessive amounts of energy from AS. Since the main sources of AS were energy-dense, nutrient-poor foods, interventions which target the reduction in these foods would reduce energy and AS intake with minimal impact to core nutrient intake.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
38
3
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(49 citation statements)
references
References 32 publications
7
38
3
1
Order By: Relevance
“…Previous analysis by our group of the more recent 2007 Australian National Children's Nutrition and Physical Activity Survey (2007ANCNPAS) (14) showed similar results, with children and adolescents aged 9-16 years having the highest added sugar intake, mainly from increased sugar-sweetened beverage consumption.…”
Section: Discussionsupporting
confidence: 66%
“…Previous analysis by our group of the more recent 2007 Australian National Children's Nutrition and Physical Activity Survey (2007ANCNPAS) (14) showed similar results, with children and adolescents aged 9-16 years having the highest added sugar intake, mainly from increased sugar-sweetened beverage consumption.…”
Section: Discussionsupporting
confidence: 66%
“…However, the IOM cut-off should not be seen as a daily intake target. Although the IOM recommendation was on added sugar, it may also be applicable to free sugars, as mean daily freesugar intake is only ∼10 g higher than that of added sugars as shown in a previous study (10). Similar results should be expected regarding the correlation with nutrient dilution when intake of free sugars is high.…”
Section: Discussionsupporting
confidence: 74%
“…A previous systematic review concluded that added sugar was associated with poorer nutrient intake, which was supported by positive conclusions from 42 out of 52 studies investigating the affect of added sugar intake on diet quality (15). A similar impact on micronutrient dilution was expected from free sugars as an estimate of ∼10 g difference between added sugar and free-sugar intake was found in the Australian population (10).…”
Section: Introductionsupporting
confidence: 51%
See 1 more Smart Citation
“…While the Australian Dietary Guidelines indicates that intakes up to 15–20% of total energy from total sugars are compatible with a healthy diet, intakes in the current sample population were high. Our results are consistent with other nationally representative studies that reveal that preschoolers’ diets consist of excessive intakes of sweetened foods, such as sugar‐sweetened soft drinks and fruit juices, and this was associated with lower nutrient and food group intakes, thus negatively impacting diet quality . There is extensive evidence indicating the association between frequent sugar consumption and higher prevalence of dental caries in children .…”
Section: Discussioncontrasting
confidence: 72%